(untitled) (Bangladesh Journal of Medical Science, 2014)
Objective: This study explores how the adolescents identify diet and why do they select these types of foods as diet and how they conceptualize health. Methodology: This is an empirical study conducted applying qualitative methods in a semi-urban Muslim community at Sylhet district in the northeastern region of Bangladesh. Data were collected through in-depth interviews. Results: Adolescents had diverse conceptions on foods related to nutrition and health care. Adolescents relate food categorization mainly with the price of food, function of foods and a number of sensory characteristics, such as taste, smell and color. They categorized foods according to the price of foods- poor and rich; and to the function of foods- hot and cold. They had different preferences in different genders according to the sensory characteristics of foods- black color, sour taste etc. They had also some gender specific taboo on some foods. Conclusion: This study reveals that adolescents have diversified thinking on foods related to nutrition and health care practices, which demands to provide special attention for improving their understanding on food, nutrition and health care. DOI: http://dx.doi.org/10.3329/bjms.v13i4.19165 Bangladesh Journal of Medical Science Vol.13(4) 2014 p.391-395